SPEECH ACTS ANALYZE IN DONALD TRUMP’S SPEECH: TRUMP BANS ALL REFUGEES AND CITIZENS OF 7 MAJORITY MUSLIM COUNTRIES ENTERING U.S - Jimmi, Jimmi; Sidauruk, Juniato (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2019)
The purpose of this research is to understand and discuss about Speech Acts of the United Stated of America, Donald Trump. The speech will be discussed linguistically by the writer. In analyzing Trump’s speech, the writer will relate it to the speech acts belong to J. L. Austin, those are: locutionary act, illocutionary act, and perlocutionary act. The analysis that will be elaborated by the writer is about Austin’s types of speech acts contained in Donald Trump’s speech, and then the most and the least types used in Donald Trump’s speech, and also determining does perlocutionary is always exist in every Trump’s utterance. This research is using descriptive qualitative method. In this case, the writer found 10 utterances related to Donald Trump’s speech. In those utterances, there include 10 data of locutionary forces, 10 data of illocutionary forces, but only 2 data that show perlocutionary forces, because not all utterances conduct perlocutionary. Thus, every utterance can be linguistically analyzed, in order to see whether every speech always conduct perlocutionary forces or not.